OPTIMIZATION OF NATIONAL DEFENSE INDUSTRY CAPACITY TO ENSURE THE FULFILLMENT OF INDONESIAN NAVY DEFENSE EQUIPMENT IN SUPPORT OF NATIONAL MARITIME DEFENSE - Pandu Briantisno; Achmad Faisol; Mohamad Rachmad (Journal of Industrial Engineering & Management Research, 2026)
The dynamics of the global strategic environment, particularly in the Indo-Pacific region, require Indonesia to continuously strengthen its maritime defense through the independent and sustainable fulfillment of the Indonesian Navy’s primary weapon systems. This study aims to analyze the current capacity of the national defense industry, identify the main obstacles in meeting the Indonesian Navy’s defense equipment needs, and formulate relevant optimization strategies. The study employs a qualitative method, grounded in Law of the Republic of Indonesia Number 3 of 2002 concerning National Defense and Law of the Republic of Indonesia Number 3 of 2025 concerning the Indonesian National Armed Forces, and is supported by Defense Industry Theory and Self-Reliance Theory. The findings show that the national defense industry has made progress, particularly in the construction of several types of warships; however, it still faces limitations in mastering high-end technology, importing strategic components, research and development, and institutional synergy. SWOT analysis places the strategy in Quadrant III (turn-around), emphasizing the reduction of import dependence, strengthening mastery of strategic technology, increasing research investment, and optimizing collaboration among the government, industry, research institutions, and the Indonesian Navy. This strategy is important to strengthen the self-reliance of the national defense industry and support national defense readiness at sea.